Los Recursos Didácticos en el aprendizaje de Lengua y Literatura del cuarto grado “A”, Unidad Educativa “José Ángel Palacio” de Loja, 2021-2022. - Carrión Cuenca, Gisela Katherine (2022)
The current investigation, named: The Didactic Resources in Language and Literature learning of fourth grade, parallel “A”, of "José Ángel Palacio" school, located in Loja city, period 2021–2022, has as its general objective to determine the different Didactic Resources that help in the learning of Language and Literature area, in students of fourth grade, parallel "A" morning section of "José Ángel Palacio" school. The application of these didactic resources helped to improve the problem found. In the same way, the methodology applied was descriptive with a study of quantity-quality representation. We used different methods such as: descriptive, analytic, synthetic, inductive, deductive, statistical, and bibliographic, which helped us to give the basis to the unlike authors’ proposals and, based on these ideas, infer criteria to deep into the study topic; the population was established for twenty-one students and one teacher, who allowed us to elucidate the problem through a questions bank related to the searching work, determining as a final result that the employing of different didactic resources in Language and Literature learning simplifies the contents’ comprehension and, at the same time, keeps students motivated and focused during the class process. Keywords: Didactic Resources, Language and Literature, importance of learning, audiovisual material, didactic boards.